Analyzing the Influence of Digital Literacy and Pedagogical Knowledge on TPACK in Elementary School Teachers - Veni Veronica Siregar; Rajab; Hermansyah; Eva Ardinal; Rully Hidayatullah; Nurkhaerat Alimudin (Jurnal Ilmiah Sekolah Dasar, 2024)
The rapid development of technology requires the education sector to adapt digital literacy to make the learning process more relevant to 21st-century needs. However, many teachers have yet to master the Technological Pedagogical Content Knowledge (TPACK) framework, particularly in integrating technology into teaching practices. This study aims to analyze the influence of digital literacy on TPACK and the influence of pedagogical knowledge on TPACK among elementary school teachers. The research employs a quantitative method with an ex post facto design. A saturated sampling technique was used, involving all 35 elementary school teachers as respondents. Data were collected through structured questionnaires on digital literacy, pedagogical knowledge, and TPACK competencies. The data were then analyzed using multiple linear regression techniques. The results indicate that digital literacy has no significant influence on TPACK, with a significance value of 0.147. In contrast, pedagogical knowledge shows a significant influence on TPACK, with a significance value of 0.015. These findings suggest that while digital literacy is essential, pedagogical knowledge plays a more substantial role in improving teachers' ability to integrate technology into the learning process. In conclusion, enhancing pedagogical knowledge can strengthen teachers’ competencies in effectively utilizing technology in elementary school education.